Effect of Rust Inhibitor in Brine on Corrosion Properties of Copper. (2017) - Higuchi, Kazunari; Shohji, Ikuo; Ando, Tetsuya; Koyama, Shinji; Mizutani, Yoshikazu; Inoue, Yukio
Abstract: In this study, the effects of rust inhibitors in brine on corrosion behaviors of copper were investigated by measurement of cathode and anode polarization curves and an immersion test. For rust inhibitors, benzotriazole, sodium benzoate and sodium nitrite were prepared. From measurement results of cathode and anode polarization curves, it was found that the corrosion rate of copper in the benzotriazole solution is low and a stable passive film with excellent corrosion resistance generates on the surface of copper in the solution. In the case of the sodium benzoate solution, the corrosion resistance of the passive film was inferior to that in the benzotriazole solution although the passive film generated on the surface of copper. In contrast, the passive film scarcely generated on the surface of copper in the sodium nitrite solution. The result shows that the rust preventive effect of the solution to copper is weak. Furthermore, the immersion test revealed that the benzotriazole solution has the rust preventive effect to copper. In contrast, the effect of the sodium benzoate solution is weak and that of the sodium nitrite solution is scarcely expected.